The Role of The Construction Dispute Board in The Settlement of Construction Disputes - Yuliyanto Waisapi, Jeffery (Green Publisher Indonesia, 2023)
This study aims to analyze the role of the dispute board in the construction dispute resolution system in Indonesia. This study uses descriptive research methods. This method is used to describe and explain the phenomena that occur. The dispute board exists as an alternative to resolving construction disputes that can provide various benefits, such as saving time. The settlement of construction disputes in Indonesia is regulated in Article 88 of Law Number 2 of 2017 concerning services. In the settlement of construction disputes, the dispute Board has an important role in the settlement stages, such as mediation, conciliation, and arbitration. The dispute board can also play a role in maintaining justice and resolving disputes in a simple and friendly manner. This study analyze the position of the dispute board in the construction dispute resolution system in Indonesia and assess the existing arrangements. The results show full construction disputes occur in a contract because of differences in perception between service providers and service users so that it is necessary for a third party to be used as a facilitator to explain to each party in determining the contents of the agreement and its It is hoped that the results of this study can provide a better understanding of the role of the dispute board in the settlement of construction disputes in Indonesia.